Characterization of Co/sulfated zirconia catalysts for selective reduction of NO by methane - Quincoces, Claudia Edith (2008)
In this study, Co based catalysts (0.5-5 wt% Co) supported on sulfated zirconia were prepared for NO selective reduction by methane. The effect of Co loading on the catalyst structure, the catalytic activity and stability, as well as the deactivation rate by 6 vol% water in the feed are reported. The best results were obtained with catalysts up to 2 wt% Co loading. XPS and DRS analyses indicated the existence of the Co+2 in fresh samples. The higher activity was shown by a catalyst containing octahedral Co+2 species supported on sulfated zirconia having tetragonal-monoclinic structure. © 2008 Elsevier B.V. All rights reserved.